Fiscal policies, the current account and Ricardian equivalence - Christiane Nickel; Isabel Vansteenkiste (European Central Bank (ECB), 2008)
This paper analyses the empirical relationship between fiscal policy and the current account of the balance of payments and considers how Ricardian equivalence changes this relationship. To do so, we estimate a dynamic panel threshold model for 22 industrialised countries in which the relationship between the current account and the government balance is allowed to alter according to the government debt to GDP ratio. The results show that for countries with debt to GDP ratios up to 90% the relationship between the government balance and the current account is positive, i.e. an increase in the fiscal deficit leads to a higher current account deficit. For very high debt countries this relationship however turns negative but insignificant, suggesting that a rise in the fiscal deficit does not result in a rise in the current account deficit. Implicitly this result suggests that households in very hight debt countries tend to become Ricardian. Estimating the same model for the 11 largest euro area countries shows that the reationship between the govnerment balance and the current account turns statistically insignificant when the debt to GDP ratio exceeds 80%.
Keywords: F32; E62; F41; 330; current account; Fiscal Policy; panel threshold model; Finanzpolitik; Leistungsbilanz; Ricardianische Äquivalenz; Industrieländer